Emerging role of bio-based solvents mixtures to increase the solubility and recovery of carotenoids from processed carrot wastes for potential skin care application - Mussagy, Cassamo U.; Oshiro, Ariane [UNESP]; Farias, Fabiane O.; Haddad, Felipe F. [UNESP]; dos Santos, Jean L. [UNESP]; Scarim, Cauê B. [UNESP]; Herculano, Rondinelli D. [UNESP]; Pessoa, Adalberto; Santos-Ebinuma, Valeria C. [UNESP] (Elsevier, 2023)
Carotenoids are abundant in food waste and offer various health benefits. In response to the growing demand for sustainable technologies, this study aims to establish an efficient recovery protocol for carotenoids (β-carotene and α-carotene) from carrot waste using eco-friendly solvents. The effectiveness of 2-methyltetrahydrofuran (2-MeTHF), limonene (Lim), and cyclopentyl methyl ether (CPME) in extracting carotenoids is compared with ethyl acetate (EtOAc), a conventional green solvent commonly used to replace hexane and petroleum ether. The solubility behavior was evaluated using experimental and in silico approaches, along with assessing the hydrotropic effect, thermal stability, and antioxidant properties. Furthermore, the irritability of the recovered carotenoids has been investigated concerning potential skin care applications. The highest recovery yields of β-carotene (72.21 ± 6.21 μg/g) and α-carotene (56.11 ± 4.83 μg/g) were achieved using an EtOAc:2-MeTHF mixture, resulting in an increase of approximately 25 μg/g compared to the control (EtOAc). The EtOAc:2-MeTHF mixture indicated that approximately 37% of the carotenoids were degraded after 336 h with a Dvalue of 677 h. CAMs treated with the recovered carotenoids showed no visible response during the 300-second period, with all SI values at 0.7. The recovered carotenoids demonstrated positive biological activities and biocompatibility for use on human skin as an anti-aging agent. These results indicate that the carotenoids obtained from carrot waste have the potential for further application in the cosmetic industry.
Keywords: Antioxidant; Bio-based solvents; Carotenoids; Carrot; Cosmetic; HET-CAM assay; Waste